A method for calculating an edge version of the Wiener number of a graph operation - Azari, Mahdieh; Iranmanesh, Ali; Tehranian, Abolfazl (Utilitas Mathematica, 2012)
The edge versions of the Wiener index, based on distance between two edges in a graph G, were introduced by Iranmanesh et al. in 2009. In this paper, we suggest a method for computing one of the edge versions of the Wiener number for a graph operation.